2016
DOI: 10.1007/s00410-016-1235-y
|View full text |Cite
|
Sign up to set email alerts
|

Temporal evolution of a post-caldera, mildly peralkaline magmatic system: Furnas volcano, São Miguel, Azores

Abstract: This is considered to take place in a density-stratified reservoir, with alkali basalt magmas at the base and hydrous trachytes forming an upper cap or cupola. The presence of this reservoir at shallow crustal depths beneath the caldera likely inhibits the ascent and subsequent eruption of mafic magmas, generating a compositional Daly Gap. Rare syenitic ejecta represent in situ crystallisation of trachytic magmas in the thermal boundary zone at the top of the reservoir. Trachytic enclaves within these syenites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 92 publications
(144 reference statements)
2
39
0
Order By: Relevance
“…For the specific case of the Azores we consider the presence of large quantities of sediments unlikely due to the young age and limited quantity of sediments however, the igneous lithologies may act as a density barrier. Other central volcanoes in the Azores, for example, the neighboring Pico Alto volcano (Jeffery et al, 2017), Sete Cidades (Beier et al, 2006) and Furnas (Jeffery et al, 2016) on São Miguel, and the Caldeira volcano on Faial (Dias et al, 2007) also have shallow magma reservoirs in 2-to 4-km depth (3-7 km for the Caldeira volcano) and our barometric data for Santa Bárbara agree with these observations.…”
Section: Ponding Depth and The Role Of Fractional Crystallizationsupporting
confidence: 85%
“…For the specific case of the Azores we consider the presence of large quantities of sediments unlikely due to the young age and limited quantity of sediments however, the igneous lithologies may act as a density barrier. Other central volcanoes in the Azores, for example, the neighboring Pico Alto volcano (Jeffery et al, 2017), Sete Cidades (Beier et al, 2006) and Furnas (Jeffery et al, 2016) on São Miguel, and the Caldeira volcano on Faial (Dias et al, 2007) also have shallow magma reservoirs in 2-to 4-km depth (3-7 km for the Caldeira volcano) and our barometric data for Santa Bárbara agree with these observations.…”
Section: Ponding Depth and The Role Of Fractional Crystallizationsupporting
confidence: 85%
“…Pre-eruptive temperatures for the combined dataset exhibit considerable range, extending from around 1,050 • C for magmas with peralkaline affinity (e.g., the trachytes of Faial; Pimentel et al, 2015; the phonolites of the Granadilla eruption, Tenerife; Bryan, 2006), to ∼ 700 • C for mildly to strongly peralkaline magmas (Figure 8). This range extends down to approximately 600 • C if autolithic peralkaline syenite clasts, considered to (Putirka, 2008;Mollo et al, 2015), calculated in this study using the data of Imsland et al (1977), Storey (1981), Le , Renzulli and Santi (2000), Siebel et al (2000), Troll and Schmincke (2002), Rodriguez-Losada and Martinez-Frias (2004) (Ablay et al, 1998;Troll and Schmincke, 2002;Rodriguez-Losada and Martinez-Frias, 2004;Bryan, 2006;Dávila-Harris et al, 2013;Zanon and Frezzotti, 2013;Pimentel et al, 2015;Chamberlain et al, 2016;Eisele et al, 2016;Jeffery et al, 2016bJeffery et al, , 2017.…”
Section: Temperaturementioning
confidence: 84%
“…This process not only controls the generation of peralkaline felsic magmas from basaltic progenitors, but also controls evolutionary trends within peralkaline felsic magmas, forming felsic magmas with varying degrees of peralkalinity. There exists a wide range of published studies and quantitative models which reliably recreate the compositions observed in the magmatic systems of the Atlantic, including major element, least-squares mass balance models, thermodynamic models, and trace element models (e.g., Iceland: Carmichael, 1964;Macdonald et al, 1990;Furman et al, 1992a;Sigmarsson et al, 1992;Hards et al, 2000;Prestvik et al, 2001;Martin and Sigmarsson, 2007; Azores: Widom et al, 1992;Mungall and Martin, 1995;Renzulli and Santi, 2000;Beier et al, 2006;Larrea et al, 2013Larrea et al, , 2014aZanon, 2015;Jeffery et al, 2016bJeffery et al, , 2017Canary islands: Freundt and Schmincke, 1995;Ablay et al, 1998;Neumann et al, 1999;Sliwinski et al, 2015;Tornare et al, 2016;Cape Verde: Holm et al, 2006;Kogarko, 2008;Hildner et al, 2011;Cameroon Line: Marzoli et al, 2000;Ascension Island: Harris, 1983;Kar et al, 1998;Chamberlain et al, 2016;Bouvet Island: Le Roex and Erlank, 1982;Prestvik et al, 1999; Tristan da Cunha: Le Roex et al, 1990;Harris et al, 2000;Gough Island: Le Roex, 1985;Harris et al, 2000;St. Helena: Baker, 1969; Fernan...…”
Section: Fractional Crystallizationmentioning
confidence: 99%
See 2 more Smart Citations